Knowing the effect of black honey on the germination rate and speed of some Leguminous and grassy plants treated with commercial yeast - هدى أحمد سعيد الحديدي; فاطمة إبراهيم بن عامر (African Journal of Advanced Pure and Applied Sciences, 2026)
his experiment was conducted in the water research laboratory of the department of Soil and Water faculty of agriculture, university of Tripoli. During month of April 2023, according to the (split-plot design) at the rate of 30 seeds per ptridish which divided to 3 replicates refared to the concentration (0-4-8-12 gm/L) in order to study the effect of the addition and non addition of Egyptian black honey product made from the Saccharum spp. with yeast extract (Saccharomyces cerevisiae). Named (Parakamaia) on the growth percentage of two species of Legumes (Vicia faba L.) and (Pisum sativum L.) also another two species of Gramineases (Triticum aestivum L.) and (Hordeum vulgare L.). The results showed that the (4gm/LConc.) is the greater growth presents to all samples with black honey than that with yeast extract alone. When compared with control samples and yeast extract samples. The average of yeast extract with black honey increased the rate of growth to reach 2.7 days compared with 3.4 days by using yeast extract alone. The percent and rate of growth of large size seeds compared with the small size seeds. The 12gm/L Concentration showed less growth rate compared with the control.